Innovation strategies and performance in small firms - Baldwin, John R. 1945-; Gellatly, Guy (E. Elgar, 2003)
John Baldwin and Guy Gellatly find that the strategic decisions young firms make play a critical role in determining their odds for survival and growth. New small firms survive by developing a core set of business skills – skills related inter alia to management, human resources, marketing and financing. Advanced innovation capabilities related to R&D and technology set high-performance firms apart from other businesses. Industry-level differences in product lifecycle, production activity, competitive intensity and the science base all influence the nature of small-firm innovation
Includes bibliographical references and index
Keywords: Innovationsmanagement; Klein- und Mittelbetrieb; Technischer Fortschritt; Small business / Management; Strategic planning; Small business / Technological innovations